Sintesis Nitroselulosa dari Serat Daun Nanas sebagai Sumber α-Selulosa untuk Bahan Baku Pembuatan Propelan - Al'farisi, Cory Dian; Padil, Padil; Yelmida A.; Nurfatihayati, Nurfatihayati (Department of Chemical Engineering, Faculty of Engineering, UNRI, 2025)
Nitrocellulose is an important compound in the chemical industry, which has various crucial applications, such as the main ingredient for making quality paint, ink, and coating formulations in the printing process, as well as a propellant (explosive). Nitrocellulose as a raw propellant material is currently very popular. In this research, pineapple leaf waste has been processed as a raw material for making nitrocellulose through a nitration process. The research aims to determine the effect of the nitration process's length and the nitrating acid's composition on nitrocellulose's nitrogen content. Before the nitration process, an initial process is carried out, namely pre-treatment of pineapple fiber to obtain fiber with a cellulose purity of >92%. In the nitration process, the ratio of titrating acid (H₂SO₄:HNO₃) used is 1:3, 1:2, 2:1, 7:3, and 3:1 with a nitration time of 30, 60, 90, and 120 minutes. The results obtained in this research were that the pre-treatment process was able to increase the purity of cellulose in pineapple fiber by up to 93%. Then the 2:1 titrating acid formulation (H₂SO₄:HNO₃) is the best acid ratio formulation. Meanwhile, the optimum time for nitration is 60 minutes, with a nitrogen content in nitrocellulose of 12.73%. Fourier Transform Infrared (FTIR) analysis shows that there has been an exchange of hydroxyl groups in nitrocellulose with nitro groups, which is indicated by the presence of a peak indicating the nitro group. Apart from that, the burning test also showed that nitrocellulose can be burned faster than cellulose